Evaluation of Pharmacokinetic Parameters of Cefquinome in Marathwadi Buffalo Calves, India - M. K. Patil; A. P. Somkuwar; P. V. Patil (Innovations in Biological Science Vol. 10, 2024)
The pharmacokinetics of cefquinome are studied in different animals such as camel, sheep, piglets, chicken, mice, dogs, pigs, and calves. However, these studies are conducted in different parts of the world and there is no data available from India. Therefore, this study aims to evaluate the Pharmacokinetic parameters of Cefquinome in Marathwadi Buffalo Calves. An experiment was performed on six healthy Marathwadi buffalo calves of either sex of age above 6 months and weighing between 80 to 120 kg to study the different pharmacokinetic parameters after a single intravenous administration @ 2 mg/kg body weight by microbiological assay technique. After intravenous administration of the drug, blood samples (4 ml each) of buffalo calves were collected from the external jugular vein using disposable needles in clot activator tubes at different time intervals. The schedule of blood collection for pharmacokinetic studies after intravenous administration was at 0, 5, 10, 15, 30 min and 1, 2, 4, 6, 8, 10, 12 and 24 hrs. The serum levels of cefquinome were estimated by microbiological assay technique using a large glass plate. Different Pharmacokinetic parameters were calculated as described by different scientists and analyzed by randomized block design, and the significance was tested at 5% and 1% levels as per. The peak serum concentration, elimination half-life, volume of distribution, total body clearance, absorption half-life and area under curve values found were 1.74 ± 0.151 mcg/ml at 2.5 min of sampling time, 1.97±0.14 h, 3.97 ± 0.83 L/kg (Vd(B)) and 2.86 ± 0.34L/kg (Vdss), 1.11 ± 0.13 L/kg.h-1, 0.10 ± 0.02 h, and 1.93 ± 0.23 µg/ml/hr respectively. The bioavailability of cefquinome in buffalo calves was found to be 165.38 %. It may be concluded that the elimination half-life of cefquinome was 2.54 h in Marathwadi buffalo calves indicating the repeating of doses at 12 to 15 h intervals in Marathwadi buffalo calves and the loading dose would be double than the maintenance dose of cefquinome after intravenous administration. The microbiological assay technique was found to be suitable for the estimation of serum cefquinome concentration in laboratories where the LC/MS facilities are not available.